Coffee in the Imagination of Arabic Poetry: A Linguistic and Cultural Symbolism Study - Afandi, Zamzam (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
The growing scholarly interest in cultural symbolism in literature indicates that everyday objects are increasingly interpreted as constructions of identity, spirituality, and affective expression. In the context of Arabic poetry, coffee emerges as a symbol whose meaning expands beyond its material function to become an aesthetic, existential, and mystical representation within poetic imagination. This study examines the symbolism of coffee in Arabic poetry as a complex semantic field encompassing spiritual, affective, and existential dimensions. Employing a linguistic-semantic and semiotic approach, this research demonstrates that coffee in poetry is not merely a cultural object, but a symbolic construct that shapes poets’ experiences of love, ecstasy, loss, and identity. The critical discussion related these findings to Roland Barthes’ theory of mythology (1972), Lakoff and Johnson’s conceptual metaphor theory (1980), and Homi Bhabha’s concept of liminal space (1994). This study demonstrated that Arabic poetry does not merely reflect culture, but actively produces new meanings through the symbolization of several objects. Coffee, in this sense, becomes a point of convergence between spirituality and the profane world, between body and language, and between memory and resistance. The primary contribution of this study lies in its assertion that everyday objects in poetry can function as symbolic axes of civilization. Accordingly, Arabic poetry may be read as a linguistic and cultural laboratory in which human experience is encoded, negotiated, and interpreted through language.